A Retrospective Multicenter Real-World Study to Determine the Efficacy and Safety of PHESGO in HER2-Positive Breast Cancer from a Community Oncology Practice in Western India - Maheshwari, Udip; Maniar, Vashishth; Joshi, Ashish; Kalaskar, Pritam; Joshi, Kshitij; Morzaria, Disha; Kendre, Pradip; Sheth, Smit; Pethe, Chandrashekhar; Dhande, Sonal; Jagiasi, Seema; Sethjiwala, Taha; Chaudhari, Krushna (Indian Journal of Medical and Paediatric Oncology, 2025)
The treatment landscape for HER2-positive breast cancer has evolved with the introduction of targeted therapy using trastuzumab and pertuzumab. Though effective, intravenous (IV) administration presents challenges like infusion-related reactions and logistical issues, affecting patient adherence and quality of life. The advent of the subcutaneous (SC) formulation of PHESGO has emerged as a promising alternative, which enhances patient experience and adherence in the treatment of HER2-positive breast cancer.This study evaluates the efficacy, safety, and patient preference of PHESGO in a real-world setting.This retrospective analysis included 30 patients with HER2-positive breast cancer receiving PHESGO as monotherapy or in combination with chemotherapy. Inclusion criteria encompassed patients aged 18 to 80 with comprehensive medical records and documented survival status. Data were extracted from electronic medical records to evaluate treatment efficacy, adverse events, and patient satisfaction, using validated Patient Preference and Therapeutic Antibody Satisfaction Questionnaire - Subcutaneous Injection (TASQ-SC) questionnaires.The median (interquartile range) age was 53.5 (18.0) years, with most patients at cancer stage IV (36.7%). PHESGO achieved an 86.7% objective response rate (ORR) and 76.7% [95% CI: 59.07–88.21] progression-free survival over a median survival duration of 496 days. Nearly 90% of the patients remained alive at the end of the observation period. Among neoadjuvant chemotherapy patients, a 75.0% pathological complete response rate was observed. All participants (100%) preferred SC administration, citing greater comfort and reduced clinic time, with 89.5% reporting minimal pain.The findings indicate comparable efficacy and a favorable safety profile of PHESGO relative to traditional IV administration. The high levels of satisfaction and preference for SC administration suggest that PHESGO not only meets clinical efficacy standards but also meaningfully enhances the overall patient experience.
Keywords: breast neoplasms; trastuzumab; pertuzumab; drug administration routes; patient preference